Delivery Uncertainty and the Efficiency of Futures Markets - Kamara, Avraham (Journal of Financial and Quantitative Analysis, 1990)
This paper examines the effects of the delivery basis risk embedded in nearly all futures contracts on efficiency tests of these markets. Examining soybean futures contracts, we show that delivery basis risk has important implications for market efficiency tests. Assuming no delivery basis risk, the market efficiency hypothesis is rejected. However, futures prices contain significant time-varying expected delivery basis and time-varying expected delivery risk premiums. Once these expected delivery basis and delivery risk premiums are accounted for, the apparent inefficiency is eliminated. Equilibrium spot prices also contain significant time-varying expected delivery risk premiums.